2012
DOI: 10.1051/radiopro/2011161
|View full text |Cite
|
Sign up to set email alerts
|

Absorbed radiation doses due to chronic ingestion of cesium-137 or strontium-90 by mice

Abstract: The knowledge of the absorbed radiation dose is essential in order to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Although the number of organs used for 137 Cs measurements were limited, the results were in agreement with previous biokinetics experiments using a similar exposure schedule [32]. Thus, based on previously published biokinetics data [32] and using dose conversion factors proposed by ICRP publication 108 [40, 41], the mean absorbed radiation dose was estimated at 4.4 ± 1.3 mGy for the adult model in these previous experiments. The absorbed radiation doses in the postnatal model and in the in utero models were slightly higher.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Although the number of organs used for 137 Cs measurements were limited, the results were in agreement with previous biokinetics experiments using a similar exposure schedule [32]. Thus, based on previously published biokinetics data [32] and using dose conversion factors proposed by ICRP publication 108 [40, 41], the mean absorbed radiation dose was estimated at 4.4 ± 1.3 mGy for the adult model in these previous experiments. The absorbed radiation doses in the postnatal model and in the in utero models were slightly higher.…”
Section: Resultssupporting
confidence: 87%
“…In fact, the estimated absorbed radiation dose during the lactation period was 0.30 ± 0.05 mGy, based again on these previous experiments [32]. Regarding the in utero period, a previous study showed that 85% of the absorbed radiation dose was due to the 137 Cs burden of the mother [41]. The estimated absorbed radiation dose during the in utero period was thus 0.96 ± 0.15 mGy.…”
Section: Resultsmentioning
confidence: 60%
“…The activity expressed in Bq/g of tissue in the skeletal muscle after 6 months exposure was 0.12 ± 0.09; 8.00 ± 0.11; 37.58 ± 0.20; 191.91 ± 0.50 for 0, 4, 20 and 100 kBq/l respectively, and after 9 months exposure was 0.08 ± 0.08; 10.02 ± 0.15; 46.49 ± 0.49; 278.41 ± 1.00 for 0, 4, 20 and 100 kBq/l respectively. The resulting absorbed radiation doses due to 137 Cs ingestion were calculated as previously described [46] and were 3, 15, and 75 mGy after 6 months and 6, 30, and 150 mGy after 9 months exposure to 4, 20 and 100 kBq/l of 137 Cs, respectively. Exposure to 137 Cs did not alter body weight in ApoE -/-mice at any time over the 9 months of treatment, compared with unexposed mice (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
“…The detection limit ranged from 4.2 to 12 counts per minute per sample, depending on the mass of the organ tested and the duration of the counting period. The radiation dose received by the muscle was calculated according to models developed for rodents [45], as previously described [46].…”
Section: Cs 137 Measurementmentioning
confidence: 99%
“…11,15,17,18,21,24,27,33,39,45,46,49,53,[78][79][80][81][82] These were largely adopted for calculation of organ absorbed dose and dosimetry of radionuclide-labeled compounds in preclinical experiments. [83][84][85][86][87][88][89][90][91][92][93][94][95] These computational models were also integrated in comparative Monte Carlo-based simulations studies investigating patterns of uptake and biodistribution data of radiopharmaceuticals for the purpose of dose estimation in molecular radiotherapy and diagnostic nuclear medical imaging procedures. [96][97][98][99][100][101][102][103][104][105][106][107] For external exposure to ionizing radiation, few studies reported on the calculation of organ dose conversion coefficients for small animals under ideal irradiation conditions (left lateral, right lateral, dorsal-ventral, ventral-dorsal, and isotropic irradiation directions), …”
Section: A Ionizing Radiation Dosimetrymentioning
confidence: 99%